2015
DOI: 10.5455/ijmsph.2015.0817201416
|View full text |Cite
|
Sign up to set email alerts
|

Psychological well-being and burden in caregivers of patients with schizophrenia

Abstract: Background: There is a definite paucity of Indian studies looking into the caregiver burden, psychological well-being, and the interface between them. Objectives: This work aims to study the correlation between these variables. Materials and Methods: The study sample included 100 patients with a diagnosis of schizophrenia and their caregivers, randomly selected from the patients admitted in the male and female wards of psychiatric center, Jodhpur, as per inclusion and exclusion criteria. Burden Assessment Sche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
30
3
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 31 publications
(25 reference statements)
8
30
3
4
Order By: Relevance
“…Singh et al 2012 [25] in his study 'Burden of schizophrenia on caregivers in Nepal' reported that most burden was in the area of finance and family dynamics and overall burden was moderate. Gupta et al 2014 [26] found that 80% of the caregivers have experienced moderate levels of burden. Older caregivers experienced higher burden whereas gender and educational status exerted no significant effect on burden.…”
Section: Introductionmentioning
confidence: 99%
“…Singh et al 2012 [25] in his study 'Burden of schizophrenia on caregivers in Nepal' reported that most burden was in the area of finance and family dynamics and overall burden was moderate. Gupta et al 2014 [26] found that 80% of the caregivers have experienced moderate levels of burden. Older caregivers experienced higher burden whereas gender and educational status exerted no significant effect on burden.…”
Section: Introductionmentioning
confidence: 99%
“…And psychological well-being is higher in siblings. A strong negative correlation was found between parental care and psychological well-being (Gupta A., et al, 2015).…”
Section: Resultsmentioning
confidence: 95%
“…Care giver's burden and quality of life are significantly worse for caregivers who treat patients with physical and mental illness (Amelia Rizzo, Marco Liotta, and Carmela Mento, 2014). 80% of caregivers experience moderate load levels, higher loads on older caregivers, caregivers and partners (Gupta A., et al, 2015). It was found that 8.33% of caregivers were treated with physical ailments such as diabetes mellitus and hypertension (Reena George & S. Raju, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Keluarga merupakan perawat utama yang memiliki peran penting dalam membantu pemulihan terhadap pasien skizofrenia. Akan tetapi, dalam merawat pasien skizofrenia, keluarga memiliki beban tersendiri yang berpengaruh terhadap psikologis keluarga dan keluarga berisiko mengalami gangguan mental (Geriani et al, 2015;Gupta et al, 2014; Lesibikan dan Ayinde, 2013).…”
Section: Pendahuluanunclassified